Draft genome sequence of streptococcus anginosus strain CALM001, isolated from the gut of an elderly dane - Hajar Fauzan, Ahmad; Schreiber, Lars; Marshall, Ian P. G.; Andersen, Philip Junker; Castro-Mejía, Josué Leonardo; Nielsen, Dennis Sandris (American Society for Microbiology, 2019)
Here, we present a 1.89-Mbp draft genome sequence of Streptococcus anginosus strain CALM001, a Gram-positive bacterium that was isolated from a fecal sample donated by a 70-year-old Dane enrolled in the Counteracting Age-Related Loss of Skeletal Muscle Mass (CALM) intervention study.